The Association Between Psychological Symptoms and Self-Reported Temporomandibular Disorders Pain Symptoms in Children and Adolescents - Al-Khotani, Amal; Meisha, Dalia E.; Al Sayegh, Samaa; Hedenberg-Magnusson, Britt; Ernberg, Malin; Christidis, Nikolaos (Frontiers in Oral Health, 2021)
Several studies have reported an association between temporomandibular disorder pain (TMD-P) and emotional disorders in children and adolescents. However, no studies have reported if self-reported TMD-P in Saudi Arabia is associated with psychosocial symptoms. Therefore, the current study aimed to evaluate the association between self-reported TMD-P with depression, anxiety, and somatic problems in children and adolescents in Saudi Arabia. The hypothesis was that there is an association between self-reported TMD-P and psychological symptoms among children and adolescents. The included participants were randomly selected boys and girls aged between 10-18 years, with a mean (SD) age of 14.0 (2.3) years. Out of 633 children and adolescents that were invited to participate, 466 completed all questionnaires. The questionnaires included items retrieved from the Youth Self Report (YSR) and Axis II of the Research Diagnostic Criteria for TMD (RDC/TMD) besides demographic data, medical history, and presence of oral parafunctions. To assess the presence of self-reported TMD-Pain, each participant was verbally asked two validated questions regarding the presence of TMD-P and dysfunction (2Q-TMD). Self-reported TMD-P in children and adolescents was significantly associated with anxiety, depression, somatic symptoms, and social problems (P < 0.0001). Further, the frequencies of anxiety, depression, and somatic disorders were more evident among children and adolescents who suffered from TMD-P (P < 0.0001). The odds of reporting TMD-P in children and adolescents was 1.4 times for borderline and clinical diagnosis scores for anxiety and withdrawal depression domains, and 2.6 times for the somatic symptoms’ domains. However, in the multiple regression model after controlling for possible confounders, only somatic symptoms and social scores were significant. Moreover, self-reported TMD-P was twice as prevalent among girls compared to boys. This study reports a significant association between psychosocial burden and the presence of self-reported TMD-Pain, with a stronger impact on girls than boys. Based on this finding, the current study supports that an early approach and recognition of children and adolescents with anxiety, depression, somatic symptoms, and TMD problems. This could result in a lesser burden for these children and adolescents both in regard to pain and psychosocial implications with increased quality of life.